Knowledge, Attitude, and Practice on Over-the-Counter Drugs Among Pharmacy and Medical Students: A Facility-Based Cross-Sectional Study - Bekele KM; Abay AM; Mengistu KA; Atsbeha BW; Demeke CA; Belay WS; Yimenu DK (Dove Medical Press, 2020)
Kidist Mulugeta Bekele, Ahmed Moges Abay, Kidist Abiye Mengistu, Berhanemeskel Weldegerima Atsbeha, Chilot Abiyu Demeke, Wudneh Simegn Belay, Dawit Kumilachew Yimenu Department of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Dawit Kumilachew YimenuDepartment of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, Amhara Regional State, EthiopiaTel +251 920 760 099Email dawitkumilachew@yahoo.comBackground: Self-medication with over-the-counter (OTC) medications is common among medicine and health science students. For safe use of OTC medications, students are expected to have proper knowledge, attitude, and practice (KAP) towards OTC medications and subsequent adverse drug reactions (ADRs).Objective: The aim of this study was to assess KAP of OTC medications use and related factors among medical and pharmacy students at the University of Gondar, Gondar, Northwest Ethiopia.Methods: A cross-sectional study was conducted. Data were collected using a self-administered questionnaire and analyzed using Statistical Package for Social Sciences (SPSS) version 24. Chi-square analysis was conducted and multivariable logistic regression analysis was used to determine the association between KAP and OTC use and its related adverse effects. A P value of less than 0.05 was used to declare statistical significance.Results: A total of 380 students (229 medical students and 151 pharmacy students) participated in the study. The majority of the respondents 303 (79.7%) reported that they have the practice of self-medication. Fever 69 (80.2%), headache 21 (24.4%), and abdominal cramp 20 (23.3%) were the most common conditions for which the students go for self-medication while paracetamol 51 (59.3%) followed by non-steroidal anti-inflammatory drugs (NSAIDs) 44 (51.2%) were the most commonly used classes of drugs. An intention for time-saving caused by the waiting time due to crowds in medical consultation rooms 212 (77.4%) and a desire for quick relief 171 (62.4%) were the main reasons for the self-medication practice with OTC medications.Conclusion: Self-medication is widely practiced among medical and pharmacy students. Significant problems and malpractices were identified, such as sharing of OTC medications, the use of expired medicines, doubling the dose of medications when they were ineffective, storage of OTC medications, and not reading labels and expiry dates.Keywords: self-medication, pharmacy students, medical students, over-the-counter, Gondar